Tingkat Return On Ekuitas Pada UKM Mart Dharma Karya Palembang Periode 2015-2019 - Karlina, Ani; Lupikawaty, Marieska; Djumrianti, Desloehal (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2021)
This study describes the condition of the financial performance of UKM Mart Dharma Karya Palembang in the 2015-2019 period. This study used secondary data in the form of income statements for the last five years. Methods of data collection are carried out by means of interviews, documentary observations, and library research. The results showed that the financial performance of Mart Dharma Karya UKM during the last five years was considered very poor. This shows that the company has not been able to manage its finances effectively based on profitability ratios, namely return on equity which is considered very poor and continues to decline. As for the efforts that must be made by the company to increase the equity generated from the remaining operating results (SHU), namely by adding new members to join the KPRI Dharma Karya Palembang Cooperative.